Love: Truth or Consumption? - Salobral Martín, Nieves (Investigaciones Feministas (Feminist Research), 2015)
The Christian notion of love was created by Augustine of Hippo, and remains alive in our social imaginary. Love is defined as the movement of longing for the desired object that is satisfied in the fusion with the loved one, so that happiness is achieved by this unit. Two loving models considered in the analysis: caritas and cupiditas, is identified as the first and second true as wrong. One of the most elaborate corporal inclinations and modifications is the symbolic order of male domination; that it is also an essential device for loving socialization. This disciplinary procedure on bodies predisposes them to build two different ethics: the ethic of care and responsibility and the ethic of justice and rights Capitalism presents love as an object of consumption to become a fetish of the market. And both moral identities must reach love to fulfill ethical mandate.
Keywords: Caritas; Cupiditas; Ethic; Domination; Consumption